2021
DOI: 10.3390/app11083332
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Chronic Exposure to Pesticide Methomyl on Antioxidant Defense System in Testis of Tilapia (Oreochromis niloticus) and Its Recovery Pattern

Abstract: The chronic effect of environmental methomyl on the antioxidant system in testis of Nile tilapia (Oreochromis niloticus) and its recovery pattern was investigated. Tilapia were exposed to sublethal concentrations of 0.2, 2, 20 and 200 μgL−1 methomyl for 30 days and thereafter moved to methomyl-free water for 18 days. Antioxidant levels in testis, including glutathione peroxidase, catalase, glutathione-S-transferase, glutathione reductase, superoxide dismutase, reduced glutathione, oxidized glutathione were mea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 29 publications
1
3
0
Order By: Relevance
“…On the other hand, those groups were higher than group I in GSSG levels. The earlier evidence in another pesticide supported our data; in an in vitro experiment, exposure to methomyl significantly decreased GSH but elevated GSSG levels [66]. We have observed that N. nucifera extract was found to adjust the GSH and GSSG close to the normal range in groups VII-IX when compared to Mz-treated alone.…”
Section: Discussionsupporting
confidence: 90%
“…On the other hand, those groups were higher than group I in GSSG levels. The earlier evidence in another pesticide supported our data; in an in vitro experiment, exposure to methomyl significantly decreased GSH but elevated GSSG levels [66]. We have observed that N. nucifera extract was found to adjust the GSH and GSSG close to the normal range in groups VII-IX when compared to Mz-treated alone.…”
Section: Discussionsupporting
confidence: 90%
“…However, epidemiological data are not available for all health issues. It has been documented that various chronic diseases and disorders occur after people have been exposed to pesticides [117][118][119], including cancers, adverse reproductive outcomes [120], male sterility [121], peripheral neuropathies [122], neurobehavioral disorders [123], impaired immune function (Nankongnab et al, 2020) [124], and allergic sensitization reactions, particularly of the skin [125][126][127]. Moreover, most of the pesticides examined affect male reproductive systems [124][125][126][127][128], causing sperm damage [118], DNA damage [129], and abnormal sperm morphology [13].…”
Section: Chronic Diseasementioning
confidence: 99%
“…The nominal concentrations of methomyl were set as 0 (control), 0.2, 2, 20, and 200 µg L −1 , respectively, and each group had three replicates. The concentration of methomyl ranges was chosen according to the following information: the 96-h LC 50 of methomyl to tilapia (430 µg L −1 ) from our previous research [7]; the residue levels of methomyl reported in the natural environmental water was in the range of 0-55.3 µg L −1 [2]; the maximum permissible concentration for methomyl in drinking water of 200 µg L −1 published by the United States Environmental Protection Agency (EPA) in 2012. Half of the water in the tank was changed daily, and methomyl was added as needed to maintain the nominal concentrations.…”
Section: Experimental Designmentioning
confidence: 99%
“…Methomyl residues in concentrations as high as 55.3 µg L −1 have been reported in natural water [2]. Because methomyl is often detected in natural water bodies and has the potential to disrupt the endocrine system in animals [3], its toxicity to aquatic animals has attracted extensive attention [4][5][6][7].…”
Section: Introductionmentioning
confidence: 99%